Law Schools and the Market for International Postgraduate Students - Peter Devonshire (Legal Education Review)
Public law need no longer be bound by the traditional fields of constitutional and administrative law. In a contemporary context, it has the scope to encompass statutory construction, human rights, state sovereignty, electoral law, legal philosophy, and the rule of law amongst others. In short, an expanded conceptualization of public law speaks to government power. While public law’s horizon is expanding, so too is academic practice. No longer the domain of discrete enterprises of teaching, research and engagement, academic practice can now be conceptualized as a coherent scholarly enterprise mediated by digital technologies. This article first articulates the meaning of an expanded public law and integrated scholarly practice. It then explores how the digitally literate public law academic can put this into practice. Through the use of two case studies, it describes how democratizing digital media offer a context for and means of community engagement and education in public law issues while they are in the public eye. As academic practice, the teaching moment of contemporary public law in action offers an opportunity for broadening both academic and student horizons.